Matate, Débil, Precoz: derivas del lenguaje en la trilogía de Ariana Harwicz (Dossier: Producir presente: tocar el cuerpo, escritura, mujeres, paisajes, afectos. Narrativa contemporánea de escritoras en América Latina) - Ponce Padilla, Gabriela (2018)
The trilogy by Argentinian writer Ariana Harwicz, which brings together the novels Matate, amor, La débil mental y Precoz, is analyzed in this article with basis on the ways in which language translates and materializes the experience of the female body as traversed by the violent and paradoxical presence of the maternal.